Institutional Governance and Its Role in Reducing Financial and Administrative Corruption in Islamic Banks Operating in The City of Hebron - Abueid, Raed; Shawar, Alaa; Khmaisah, Ayat (International Journal of Shari’ah and Corporate Governance Research, 2020)
The aim of this research is to identify the institutional governance and its role in reducing financial and administrative corruption in Islamic banks operating in the city of Hebron, and a questionnaire has been built to answer the study questions, as it was distributed to all workers in Islamic banks operating in the city of Hebron. The study concluded that Corporate governance has a major role in reducing financial and administrative corruption in Islamic banks operating in the city of Hebron, due to the Board’s enjoyment of competence, competence, independence, and integrity, as well as because Islamic banks maintain independent, impartial and effective auditing systems that achieve compliance with what Enhanced disclosure and transparency. The study recommended that the standards of corporate governance be strengthened in reducing financial and administrative corruption by activating the role of oversight within banks through seminars and training necessary to qualify employees in banks, and that banks support independent, fair and effective auditing systems to achieve compliance during the performance of activities Banking.